Penegasan Superioritas Kristus Dalam Surat Ibrani 1:1-4 Guna Membungkam Adopsionism - Rendi Risky Laowo; Abad Jaya Zega (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
For centuries, Christianity has experienced very serious problems regarding the doctrine of Christology. Until now, this problem is still a matter of polemic and debate, both among theologians, the Church, and even ordinary congregations. Often the errors regarding Christological doctrine stem from the understanding of Adoptionism. Where they assume that Jesus was appointed as the Son of God and has no equality in the relationship of teh Trinity. Of course, this wrong assumption affects the people and destroys true faith. So it is important for God’s people to have a foundation of faith that holds firmly to God’s infallible revelation. So that every believer has a shield of faith that is strong and can stand the test. In this way God’s people can silence misleading teachings such as Adoptionism.